Integration Of Pesantren Values In The Construction Of A Religious Society: A Study Of Local Government Policy In Bondowoso Regency - Rifa'i Rifa'i; Rusydi Rusydi (Universitas Nurul Jadid, 2025)
This study analyzes the institutionalization of pesantren (Islamic boarding school) values within regional governance to construct a religious society. Using a qualitative ethnographic case study, the research explores how local government policies transform traditional religious ethics into formal legal frameworks. Data were gathered through participant observation, document analysis, and in-depth interviews with cross-sectoral stakeholders, including legislative leaders, executive bureaucrats, and spiritual authorities. Findings reveal that the integration of pesantren values transcends symbolic programming, manifesting as a hybrid governance model that synergizes bureaucratic rationality with transcendental authority. The formalization of these values into local legislation has reconfigured public compliance, where civic duty now intersects with spiritual loyalty. This process facilitates a